Intermediate Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-894-7
ISBN 13: 978-0-13417-894-3

Chapter 7 - Section 7.7 - Complex Numbers - Exercise Set - Page 570: 95



Work Step by Step

Note that $(-i) = -1(i)$ Thus, the given expression is equivalent to: $=[-1(i)]^4$ Use the rule $(ab)^m = a^mb^m$ to obtain: $=(-1)^4(i)^4 \\=1(i^4) \\=i^4$ RECALL: (1) $a^{mn} = (a^m)^n$ (2) $i^2=-1$ (3) $a^{m+n} = a^m \cdot a^n$ Use rule (1) above to obtain: $i^{4}=(i^2)^{2}$ Use rule (2) above to obtain: $=(-1)^{2} \\=(-1)(-1) \\=1$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.